2014
DOI: 10.1007/s10461-014-0886-9
|View full text |Cite
|
Sign up to set email alerts
|

Time Since Release from Incarceration and HIV Risk Behaviors Among Women: The Potential Protective Role of Committed Partners During Re-entry

Abstract: After release from incarceration, former female inmates face considerable stressors, which may influence drug use and other risk behaviors that increase risk for HIV infection. Involvement in a committed partnership may protect women against re-entry stressors that may lead to risky behaviors. This study measured the association between time since release from incarceration (1-6 months ago, and >6 months ago versus never incarcerated) and HIV risk behaviors and evaluated whether these associations differed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
0
11
0
5
Order By: Relevance
“…Research has shown that women who engage in more HIV risk behaviors, such as injection drug use and risky sexual practices, are also more likely to cycle in and out of the criminal justice system (39). Studies have also shown that the community re-entry period following incarceration is a time of heightened risk for women to relapse to high-risk drug use, including IDU and casual sexual practices (40). Thus, consistent with the findings from the current study, the jail provides both an ideal venue and a critical opportunity to identify and intervene with women who are highest risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that women who engage in more HIV risk behaviors, such as injection drug use and risky sexual practices, are also more likely to cycle in and out of the criminal justice system (39). Studies have also shown that the community re-entry period following incarceration is a time of heightened risk for women to relapse to high-risk drug use, including IDU and casual sexual practices (40). Thus, consistent with the findings from the current study, the jail provides both an ideal venue and a critical opportunity to identify and intervene with women who are highest risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…No tocante ao apoio social dos participantes, embora em alguns estudos o uso de crack e a situação de rua sejam apontados como questões associadas ao rompimento radical de vínculos familiares (SELEGHIM et al, 2011;JORGE, 2014;HEARN et al, 2015;SOCCOL et al, 2014), identificou-se, no presente estudo, que a maioria dos participantes tinha vínculo com suas famílias, inclusive esses eram considerados como importantes fontes de apoio emocional e material. Tal resultado corrobora estudo desenvolvido nos EUA com usuários de drogas em situação de rua, em que também se apontou a família como importante fator de proteção relacionado aos indicadores de saúde mental (NYAMATHI et al, 2012).…”
Section: Discussionunclassified
“…A partir da leitura desses artigos, identificou-se que, nos estudos recentes sobre a temática, têm-se focado principalmente as características da rede social dos usuários (GRIFFIN; RODRIGUEZ, 2011;RUDOLPH et al, 2011;JONAS et al, 2012;LATKIN et al, 2012;NYAMATHI et al, 2012;WENZEL et al, 2012;BUTTRAM;KURTZ;SURRAT, 2013;RUDOLPH et al, 2013;BOODRAM;MACKESY-AMITIA, LATKIN, 2015;KING;LATKIN, DAVEY-ROTHWWLL, 2015;SONG;WENZEL, 2015;SCHERER et al, 2016;SMITH et al, 2016), os fatores de risco, da rede social, em relação ao uso de drogas (DOHERTY et al, 2011;RHOADES et al, 2011;TOBIN et al, 2011;CRAWFORD et al, 2013;KELLY et al, 2013;MAUSLBY et al, 2014;GUNN;CANADA, 2015;FUJIMOTO et al, 2016) e os fatores de proteção, da rede social, em relação ao uso de drogas (BOOTH et al, 2011;TRENZ et al, 2012;CHARLEBOIS et al, 2012;OSER, LEUKERFELD, 2012;RAMASWAMY et al, 2013;SAPRA et al, 2013;HUDSON;NANDY, 2014;JORGE, 2014;HEARN et al, 2015;CUCCIARE et al, 2016;HORTA et al, 2016;MCNEIL et al, 2015).…”
Section: Revisão De Literaturaunclassified
See 2 more Smart Citations